Analisis Dampak Putusan Mahkamah Konstitusi Terkait Perselisihan Hasil Pemilihan Umum (PHPU) Pilpres 2024 Terhadap Kualitas Demokrasi Indonesia - Najah, Savinatun; Marchela Putri, Dewi Ayu; Zhiana Huzaini, Ike; Hayat (Idarotuna : Journal of Administrative Science, 2024)
The purpose of this study is to ascertain and assess the effects of the Constitutional Court's ruling on the dispute surrounding the outcome of the 2024 presidential election, particularly with regard to Indonesia's level of democracy. Research on the Constitutional Court's function as a defender of democracy inside the framework of the constitution will also be included. This research is based on the provisions of Article 24C of the 1945 Constitution and Law Number 24 of 2003 regulating the Constitutional Court. In order to provide a strong basis for the discussion and substance of the article, the research method for this article is a literature review, which entails gathering data from books, journals, and articles as well as references from them. The investigation's conclusions demonstrate that the Constitutional Court denied each and every request made by candidates for president and vice president, number one and number three, citing moral concerns rather than a lack of legal basis for their requests. This decision seriously threatened Indonesia's democratic system by allowing acts of nepotism, corruption, and collusion, among other harmful effects on the nation's democratic ideals. The business community, academia, and other sectors are also influenced in different ways, in addition to the general population.